ANALISIS CIYCLE COSTING DAN WASTE MANAGEMENT SCENARIOS PADA KOLAM IKAN 4G DAN AZOLLA - Listya Sugiyarti; Nur Asmilia (Sekolah Menengah Kejuruan (SMK) Pustek, 2020)
One of Mina Kahuripan fish cultivators in Jampang village located in Bogor Regency has innovation and achievements in managing fish and its fish feed, and is the largest fish producer in Bogor Regency. One of the innovations of fish cultivators is the use of a 4G (Four G) fish pond. Besides the fish pond innovation, there is another innovation, namely the use of the Azolla plant. This research aims to analyze the collaboration between Azolla and the 4G pond in waste management scenarios and cycle costing. This research is a qualitative research phenomenon. The data collection technique is done by using observation, interview, documentation, and experiment techniques. Respondents of this study were fish cultivators Mina Kahuripan in Jampang Bogor Village. The results showed that the cycle costing analysis between conventional and 4G fish ponds, it was seen that the production costs in conventional ponds were higher because the media used were all purchased by new categories, while the production costs for 4G fish ponds were lower even though there was a budget for Azolla plant ponds, the quality of the fish produced was guaranteed. Lower production costs are due to the fish cultivators doing waste management from the waste in making 4G fish ponds, resulting in cost efficiency. Another advantage of Waste management scenarios utilizes waste from vegetable and fruit plants that are above the 4G fish pond